2020
DOI: 10.1371/journal.pone.0226888
|View full text |Cite
|
Sign up to set email alerts
|

Complementary transcriptome and proteome profiling in the mature seeds of Camellia oleifera from Hainan Island

Abstract: Camellia oleifera Abel. (C. oleifera), as an important woody tree species producing edible oils in China, has attracted enormous attention due to its abundant unsaturated fatty acids and their associated benefits to human health. To reveal novel insights into the characters during the maturation period of this plant as well as the molecular basis of fatty acid biosynthesis and degradation, we conducted a conjoint analysis of the transcriptome and proteome of C. oleifera seeds from Hainan Island. Using RNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…From a total of 34016 spectra, 323 proteins were identified (Fig 2). This number is similar to protein numbers reported for shotgun seed proteomics of soybean and quinoa seeds, (243 and 352 respectively) [75,76], although less than the number of proteins identified in seeds from the tree Camellia oleifera (1691 proteins) [77], or from rice and barley grains (822 and 1168 proteins, respectively) [78,79].…”
Section: Discussionsupporting
confidence: 83%
“…From a total of 34016 spectra, 323 proteins were identified (Fig 2). This number is similar to protein numbers reported for shotgun seed proteomics of soybean and quinoa seeds, (243 and 352 respectively) [75,76], although less than the number of proteins identified in seeds from the tree Camellia oleifera (1691 proteins) [77], or from rice and barley grains (822 and 1168 proteins, respectively) [78,79].…”
Section: Discussionsupporting
confidence: 83%
“…However, information regarding the metabolic mechanisms underlying fatty acid biosynthesis in C. oleifera on Hainan Island is still limited. It needs to be stated that we have previously performed a comprehensive proteomic and transcriptomic analysis on the mature seeds of this plant by using a shotgun qualitative approach and RNA-seq technique (Illumina HiSeq X Ten platform) and preliminarily revealed the characteristics of fatty acids in seeds at the maturity stage 22 . On this basis, the present study further elucidated the dynamic changes in the functional protein profile and its mRNA transcriptional level during seed ripening of C. oleifera on Hainan Island via an iTRAQ-based quantitative method and RNA-seq technology (Illumina NovaSeq platform).…”
Section: Discussionmentioning
confidence: 99%
“…For the degradation of fatty acids in mitochondria, ACAT can facilitate the condensation of two acetyl-CoAs to yield acetoacetyl-CoA, a common starting substrate for metabolite production 65 . We have previously demonstrated that this protein is the central one in the interaction network due to its strong relationships with many other proteins involved in lipid metabolic processes 22 . Two DAPs and five DEGs whose expression levels changed significantly during seed maturation were also identified in this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations